Prevention of hypertension-induced vascular dementia by Lactobacillus paracasei subsp. paracasei NTU 101-fermented products - Meng-Chun Cheng; Tzu-Ming Pan (Taylor & Francis Group, 2017)
Context: Numerous etiological studies have established positive clinical association between hypertension and vascular dementia (VaD). Lactobacillus paracasei subsp. paracasei NTU 101-fermented products have been shown to decrease vascular risk factors such as hypertension, atherosclerosis, hyperlipidemia and obesity. Objective: This study investigated the effect of ethanol extract of Lactobacillus paracasei subsp. paracasei NTU 101-fermented products (NTU101F) in hypertension-induced VaD in rats. Materials and methods: Hypertension was promoted by subcutaneous injection of deoxycorticosterone acetate (DOCA, 25 mg/kg body weight/day, twice a week) and substitution of drinking water with 1.0% NaCl and 0.2% KCl. The NTU101F groups (0.5, 1.0, and 5.0) administered NTU101F at the concentrations 11, 22, and 110 mg/kg body weight/day, respectively, starting from day 51 day of DOCA-salt treatment. Morris water maze (MWM) was used for testing learning and memory. Different biochemical estimations were used to assess oxidative stress and inflammatory response in hippocampus. Results: Oral administration of NTU101F in DOCA-salt hypertension-induced VaD rats resulted in a significant decrease in blood pressure by 18.3-23.2% (p < 0.001), which was regulated by increasing eNOS density (about 3-fold) in the aorta, promoting NO production, and decreasing of matrix metallopeptidase 9 activity (about 2-fold) in the hippocampus, in addition to improve the kidney function and structure, decrease escape latency and increase the times spent in the target quadrant by 23.5-27.8% (p < 0.05). Conclusion: Overall, our findings suggest that NTU101F could exert neuroprotection in the brain and attenuate hypertension-induced VaD.